Рабство в Вавилонии VII-IV вв. до н.э. (626-331 гг.) - Дандамаев, M. A. (1974)
Dandamajev, M. A.; Die Sklaverei in Babylonien, 7.-4. Jahrh. v. u.Z. (626-331); engl. Résumé 477- 486; Texte in Umschrift.